Exploring cutoff points and measurement invariance of the Brunnsviken brief quality of life inventory - Hlynsson, Jón Ingi; Lindner, Philip; Barri, Bushra; Carlbring, Per (Frontiers in Psychology, 2024)
Introduction Quality of life (QoL) can be defined as the goodness of life, beyond simply absence of disease or functional impairments, self-rating scales of which capture valuable information beyond change in primary outcomes. This study (n = 3,384) validated the Brunnsviken Brief Quality of Life Inventory (BBQ) across divergent groups by evaluating its measurement invariance (MI). We hypothesized measurement invariance for the BBQ across age groups, genders, depression, and anxiety severity. Potential cutoff points for the BBQ were also explored. Method Confirmatory factor analysis (CFA) models were fit to sample data obtained from an ongoing study on transdiagnostic internet-based treatment modules. Parameters were successively constrained to assess configural, metric, scalar, and residual invariance factor structures across different groups. Results The BBQ demonstrated MI at the metric level and partial MI at the scalar level across all these groups, which remained stable at the strict-residual level for all groups except for genders. These results remained stable after correcting for unbalanced group sizes for gender, clinical–subclinical levels of depression, and clinical–subclinical levels of anxiety. A cutoff point analysis revealed that a BBQ total scores below 39 was associated with notable psychopathology. Discussion The BBQ is a reliable measure of QoL that is applicable for various divergent groups (e.g., vulnerable persons), and thus a viable instrument for use in healthcare and research with minimal aversive impact. Clinical trial registration: NCT05016843.